Collaborating for Digital Transformation How Internal and External Collaboration Can Contribute to Innovate Public Service Delivery - Verhoest, Koen; Hammerschmid, Gerhard; Rykkja, Lise H.; Klijn, Erik H. (Edward Elgar Publishing, 2024)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. As worldwide institutions acknowledge the necessity of digital, open, and collaborative governments, this timely book offers a comprehensive exploration of digital transformation, intergovernmental collaboration, collaborative governance, and public sector innovation.